Teacher professionalism and role perception in Bangladesh - Quddus, S. M. Abdul (IIUM Press, 2011)
This study made an attempt to explore professional role orientation of schoolteacher in Bangladesh in terms of their professional performance and motivation. This study shows that well-trained and motivated teachers are the key to any education system but because of the political/ electoral interest in the occupation the government policies toward primary education and teaching occupation in particular are targeted to establish state authority over the activities of teachers and their vocational life. Moreover, primary teachers in Bangladesh belong to trade-union type organization instead of ‘knowledge base’ organization of occupational group. Different political parties backed vocational associations and their distinctive ideologies has resulted lack of interest articulation of the practitioners. At the same time schoolteachers fail to have access into the process of management and delivery of their services and remain powerless. Moreover, mentality of schoolteachers is to attend respective vocational training program only due to system demands and also to get on to a higher pay scale. Their training does not match to the purpose of their occupational development and poor quality of training as well as poor academic competence resulted ineffective teaching in the classroom and de-professionalized teaching occupation in primary sub-sector in Bangladesh. As primary education is nationalized and free, and the state is the ultimate user of the vocational services of primary schoolteachers, thus the power, resources and prestige of primary teaching occupation depend largely on the policies of the Bangladesh state to which it is subject. So, the state has to decide whether it will act as regulator of primary teaching occupation or instruments of its professional advancement.